2021
DOI: 10.1177/1948550621992973
|View full text |Cite
|
Sign up to set email alerts
|

Partners’ Attachment Insecurity and Stress Predict Poorer Relationship Functioning During COVID-19 Quarantines

Abstract: The COVID-19 pandemic presents acute, ongoing relationship challenges. The current research tested how (1) preexisting vulnerabilities assessed prior to the pandemic (attachment insecurity) and (2) stress as couples endured a mandated quarantine predicted residual changes in relationship functioning. Controlling for prequarantine problems, relationship quality, and family environment, greater partners’ attachment anxiety predicted greater relationship problems, lower relationship quality, and a less stable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
73
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 62 publications
3
73
0
3
Order By: Relevance
“…Finally, individual factors which have been shown to increase vulnerability for IPV victimization (e.g., Widom et al, 2014) and are theorized to disrupt relationships (Overall et al, in press; Pietromonaco & Overall, 2020) were accounted for to examine the unique associations between COVID-19 stressors, IPV victimization, health, and health behaviors. Specifically, we assessed attachment insecurity, adverse childhood experiences, and (lower) pre-COVID-19 socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, individual factors which have been shown to increase vulnerability for IPV victimization (e.g., Widom et al, 2014) and are theorized to disrupt relationships (Overall et al, in press; Pietromonaco & Overall, 2020) were accounted for to examine the unique associations between COVID-19 stressors, IPV victimization, health, and health behaviors. Specifically, we assessed attachment insecurity, adverse childhood experiences, and (lower) pre-COVID-19 socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 99%
“…However, during the pandemic, their partner may not be able to provide reassurance because they themselves may be feeling worried about the pandemic and may not have resources themselves. Recent research has also found that anxiously attached individuals tend to act in punitive ways toward their partners which can create conflict and damage closeness ( Overall et al, 2021 ). This may have undermined the caregiving efforts from partners during the pandemic thus rendering the anxiously attached individuals more vulnerable to distress during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, which focused mainly on intimate relationships during the lockdown, indicated that high-stress levels were associated with a decline in intimate relationships [ 47 ]. Moreover, the attachment style of partners predicts interpersonal problems and the efficacy of problem-solving strategies [ 48 ]. Other studies suggested that working at home can exacerbate familial conflict [ 49 ] and that living with others contributed to increased psychological distress [ 50 ].…”
Section: Discussionmentioning
confidence: 99%